Evaluación de la eficiencia de tres dosificaciones de biol enriquecido en el frutal claudia (prunus domestica) establecido como cerca viva, CEASA-UTC, provincia de Cotopaxi, 2022. - Catota Yugsi, Edwar Wladimir (2022)
The Claudia (Prunus domestica) is located in the Sierra region as a crop of economic importance, however, the high production costs have resulted in its progressive abandonment. Therefore, the objective is: to evaluate the efficiency of three dosages of enriched biol T1 (50 ml), T2 (100 ml), T3 (150 ml) plus a witness. The research was carried out at the CEASA-UTC Experimental Center, using a completely randomized block design (DBCA) with four repetitions, where the variables were: increase in height from the base of the graft to the apex, increase in graft diameter and incidence of phytosanitary problems, the results were processed in the Infostat software, where statistical significance was found (p-value <0.05) in the increase in diameter and height of the plant in the growth stage. It was observed that for the increase in height from the base of the graft to the apex, T2 (100 ml) showed greater efficiency with a value of 24.4 cm, in terms of the increase in graft diameter it was higher in T2 (100 ml.) with 3.2 mm, it was finally observed that T3 (150 ml) had less incidence of phytosanitary problems: Leaf cutter bee (Megachile) an incidence of 3% and Shot of ammunition (Wilsonomyces carpophilus) an incidence of 5%.